Correlation of publication frequency of newspaper articles with environment and public health issues in fire-prone peatland regions of Riau in Sumatra, Indonesia - Ohashi, M.; Kameda, A.; Kozan, O.; Kawasaki, M.; Iriana, W.; Tonokura, K.; Naito, D.; Ueda, K. (Springer, 2021)
Forest fires in peatlands emit pollutants to the atmosphere, affecting public health. Though air quality data and epidemiology information are helpful in the management of the environment and public health, they are not always available. We aimed to reveal the utility of newspaper articles for estimating the public health concerns posed by air pollution. Using the database of a local newspaper, Riau Pos, in Riau Province of Sumatra, Indonesia, we have studied spatiotemporal correlations between publication frequency of newspaper articles mentioning search terms relevant to health issues and Fire Radiation Power (FRP) of peatland fires. FRP from one of the NASA satellite databases has been used as an index of air pollution caused by peatland fires. Visibility data for airport operation were also used as an index of particulate matter concentrations. The study regions are primarily the fire-prone Riau Province and nearby areas in the central area of Sumatra, Indonesia, from 2009 to 2018. Newspaper articles related to public health are found to be associated with FRP and visibility, or regional air pollution.